2019
DOI: 10.1002/anie.201811610
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis and Charge‐Carrier Dynamics of Cs2AgSb1−yBiyX6 (X: Br, Cl; 0 ≤y ≤1) Double Perovskite Nanocrystals

Abstract: A series of lead‐free double perovskite nanocrystals (NCs) Cs2AgSb1−yBiyX6 (X: Br, Cl; 0≤y≤1) is synthesized. In particular, the Cs2AgSbBr6 NCs is a new double perovskite material that has not been reported for the bulk form. Mixed Ag–Sb/Bi NCs exhibit enhanced stability in colloidal solution compared to Ag–Bi or Ag–Sb NCs. Femtosecond transient absorption studies indicate the presence of two prominent fast trapping processes in the charge‐carrier relaxation. The two fast trapping processes are dominated by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(144 citation statements)
references
References 53 publications
10
131
0
3
Order By: Relevance
“…In general, the halide ions can i ) affect the reduction potential of a salt precursor through the formation of PdX 4 2− (X=Cl − or Br − ), ii ) alter the order of surface free energies of different facets on the seed via chemisorption and thus change the relative growth rates of different facets, and iii) induce localized oxidative etching on a specific facet of the seed to initiate anisotropic growth . All these changes can impact the reduction kinetics and even reduction pathway of a precursor, enabling the formation of nanocrystals with diverse shapes . However, the understandings derived from early studies were primarily based on qualitative observations and empirical laws, in which the reduction was typically described using qualitative terms such as “slow” and “fast” and the synthesis usually involved a trial‐and‐error approach in reaching the optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the halide ions can i ) affect the reduction potential of a salt precursor through the formation of PdX 4 2− (X=Cl − or Br − ), ii ) alter the order of surface free energies of different facets on the seed via chemisorption and thus change the relative growth rates of different facets, and iii) induce localized oxidative etching on a specific facet of the seed to initiate anisotropic growth . All these changes can impact the reduction kinetics and even reduction pathway of a precursor, enabling the formation of nanocrystals with diverse shapes . However, the understandings derived from early studies were primarily based on qualitative observations and empirical laws, in which the reduction was typically described using qualitative terms such as “slow” and “fast” and the synthesis usually involved a trial‐and‐error approach in reaching the optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…But it was usually used as absorber of the solar cell rather than the light‐emitting device . Up to now, several studies have reported the synthesis of colloidal double perovskite NCs including Cs 2 AgBiX 6 (X = Cl, Br, and I), Cs 2 AgSb 1− y Bi y X 6 (X = Br and Cl; 0 ≤ y ≤ 1) and Cs 2 AgIn x Bi 1− x Cl 6 ( x = 0, 0.25, 0.5 0.75, and 0.9) NCs . The reported highest PLQY is ≈36.6% .…”
mentioning
confidence: 99%
“…The Ni 2p spectrum (Figure c) was fitted with two bands with two shake‐up satellites. The peak at 856.0 eV (Ni 2p 3/2 ) is ascribed to Ni 2+ and the binding energy at 873.6 eV (Ni 2p 1/2 ) is indexed to Ni 3+ . The S 2p spectrum (Figure d) presents two bands at 163.7 (S 2p 3/2 ) and 164.5 eV (S 2p 1/2 ), suggesting the existence of S 2− in Ni 3 S 2 .…”
Section: Resultsmentioning
confidence: 97%